Ochotona hyperborea subsp. uralensis Flerov 1927 ... - Lissovsky, Andrey A.; Obolenskaya, Ekaterina V.; Dokuchaev, Nikolai E.; Okhlopkov, Innokentiy M. (Zenodo, 2021)
Ochotona hyperborea uralensis Flerov, 1927 Ochotona hyperborea naumovi Formozov et Yakhontov, 2003 Lectotype (designated by).— Ognev 1940 ZIN 16107, adult female, skull and skin. Collected by K. K. Flerov 10.8.1926. Paralectotypes (Baranova et al. 1981): ZIN 16106, 16110, 16111. Type locality (according to museum label).— Eastern slope of Bolshoy Ural, Kharuta River, Synya River tributary (65.79°N, 62.78°E). Description.— Pikas of the B genetic lineage; northern acoustic race. The majority of the representatives of this subspecies (except for pikas from the Ural Mountains) have a clear V-shaped parietal suture (Fig. 5B). Accordingly, besides genetic identification, this subspecies can be distinguished from neighboring O. h. hyperborea by the shape of the parietal suture of the skull (Fig. 5). There are differences in the shape of the frequency modulation curve of alarm call with another spatial neighbor— O. h. cinereoflava (Fig. 6). Distribution.— The subspecies has a notably disjunct distribution—the ... : Published as part of Lissovsky, Andrey A., Obolenskaya, Ekaterina V., Dokuchaev, Nikolai E. & Okhlopkov, Innokentiy M., 2021, Intraspecific variation and taxonomy of northern pika Ochotona hyperborea (Mammalia, Lagomorpha), pp. 28-53 in Journal of Mammalogy 102 (1) on pages 37-38, DOI: 10.1093/jmammal/gyaa150, http://zenodo.org/record/7850862 ...